Differences in perceptual memory determine generalization patterns. (January 2021) - Zenses, Ann-Kathrin; Lee, Jessica C.; Plaisance, Valérie; Zaman, Jonas
Abstract: Although memory of past experiences is crucial for the ability to transfer knowledge to new situations, surprisingly little research has directly investigated the relationship between memory and generalization. The present study sought to investigate how the perceptual memory of a trained stimulus influences generalization to similar stimuli. Forty participants underwent a fear conditioning procedure on Day 1, and separate memory recall and generalization tests on Day 2. We focused on two aspects of perceptual memory: namely memory bias (i.e., over- or underestimation of stimulus magnitude) and uncertainty. We found that memory bias predicted the pattern of generalized self-reported (expectancy ratings) and psychophysiological responses (fear-potentiated startle responses). Memory uncertainty was measured in two ways: self-reported uncertainty ratings and variability in stimulus recall. We found that higher levels of self-reported memory uncertainty corresponded with a broader generalization gradient on US expectancy, while greater variability in memory recall was associated with a broader generalization gradient on fear-potentiated startle responses. Taken together, our findings suggest that memory is an important determinant of generalized behavior and illustrate the need to account for these interindividual differences in perceptual memory when examining the generalization of learned responses. Highlights: Effects of memory bias and uncertainty on fear generalization were tested. Memory and generalization were assessed in separate tasks. Memory bias affected gradients of self-reported and psychophysiological responding. Memory uncertainty led to a broadening of the generalization gradient. We demonstrated that memory is an important determinant of generalized behavior.